HLA DRB1*15:01-DQB1*06:02-Restricted Human CD4+ T Cells Are Selectively Activated With Amoxicillin-Peptide Adducts. (10th August 2020) - Tailor, Arun; Meng, Xiaoli; Adair, Kareena; Farrell, John; Waddington, James C; Daly, Ann; Pirmohamed, Munir; Dear, Gordon; Park, B Kevin; Naisbitt, Dean J
Abstract: Amoxicillin-clavulanate is the most common cause of idiosyncratic drug-induced liver injury (DILI). Drug-specific CD4+ T cells have been detected in patients with DILI, suggestive of an immune etiology. Furthermore, genetic associations including the human leucocyte antigen (HLA) DRB1*15:01-DQB1*06:02 haplotype influence susceptibility. Amoxicillin forms protein adducts that are postulated to activate T cells, by conjugating with lysine residues. However, a role for such adducts has not been described. This study aimed to (1) investigate whether amoxicillin-modified HLA-DRB1*15:01-DQB1*06:02 binding peptides selectively activate DILI patient T cells and (2) define the nature of the T-cell response with respective to antigen structure. Peptides carrying lysine residues for amoxicillin binding in positions (KP) 2-6 and anchors for the HLA-DRB1*15:01-DQB1*06:02 haplotype were designed. The amoxicillin-modified peptides were characterized by mass spectrometry prior to culturing with patient peripheral blood mononuclear cell. T-cell clones were then tested for specificity with amoxicillin, unmodified- and amoxicillin-modified peptides, and structural variants. Amoxicillin-modified KP-2 and KP-3 peptide-specific CD4+ clones proliferated and secreted interferon gamma (IFN-γ), interleukin (IL)-10, perforin and/or IL-17/IL-22 in a dose-dependent manner and displayed no cross-reactivity with amoxicillin, unmodified peptide or with positional derivatives. The T cells response was HLA class II restricted and the amoxicillin-modified peptides bound selectively to HLA-DRB1*15:01 and/or DQB1*06:02. To conclude, we show that amoxicillin-modified peptides bind to both components of the risk haplotype to stimulate DILI patient T cells and describe the importance of the position of nucleophilic lysine residue in the HLA binding peptide sequence.